2019
DOI: 10.3390/land8110170
|View full text |Cite
|
Sign up to set email alerts
|

The Land Transfer from the State Treasury to Local Government Units as a Factor of Social Development of Rural Areas in Poland

Abstract: Sustainable rural development (with the development of social functions) is currently one of the basic objectives of the rural areas policy in Poland. The main purpose of this article is to determine the level of social development of rural areas and to examine whether the National Support Center for Agriculture (NSCA) activities (in the form of transferring land to communes for the implementation of social goals) have an impact on that development, and to what extent. In this article, an assessment of the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…This study could provide beneficial enlightenment for the formulation of policies related to the system and mechanism for making the elements of "talents, lands and funds" flow to the rural areas in "Rural Revitalization Strategy". Additionally, in addition to China, many countries in the world (including developed countries such as Europe and the United States) have reported land abandonment or cannot find a suitable successor, one of the most important reasons is population migration [58,59]. In this context, the rational transfer of land can be regarded as a feasible way to prevent land abandonment and ensure food security [1,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…This study could provide beneficial enlightenment for the formulation of policies related to the system and mechanism for making the elements of "talents, lands and funds" flow to the rural areas in "Rural Revitalization Strategy". Additionally, in addition to China, many countries in the world (including developed countries such as Europe and the United States) have reported land abandonment or cannot find a suitable successor, one of the most important reasons is population migration [58,59]. In this context, the rational transfer of land can be regarded as a feasible way to prevent land abandonment and ensure food security [1,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Pomianek et al (2016) used the Hellwig's method to compare semi-urban and rural gminas in Poland analysing their socio-economic development. An assessment of the social development level of rural areas using the Hellwig method also was carried out (Rząsa et al, 2019). Pawlewicz (2015) measured the differences in development levels of urban gminas in Warmińsko-Mazurskie voivodeship in Poland.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the Hellwig's method, an approach proposed in 1968 by the Polish scientist Zdzisław Hellwig, was chosen for this study. This method is common in such type of research [25,30,[41][42][43][44][45][46][47][48][49][50]. The Hellwig's method is based on the calculation of a synthetic development index which allows the user to present a situation of diversity in the level of the phenomenon studied, covering many categories, e.g., economic, social, ecological, and spatial ones [51,52].…”
Section: X26mentioning
confidence: 99%
“…Therefore, the authors additionally studied the relationship between changes in the level of agricultural development between 2006 and 2018 and activities of the NASC. Based on the review of the literature [7,[30][31][32][33][34][35][36][37][38], it can be concluded that advancement in agriculture entails elements concerning land use, socio-demographic factors, economic factors describing agriculture, and factors determining the level of agricultural production. Following the perusal of the literature, the authors determined which features would be reliable and usable in the study.…”
Section: Introductionmentioning
confidence: 99%